Method of Calculating the Main Parameters of the Generator in Various Modes of the Car Regenerative Braking - Dvadnenko, V.; Arhun, Shch.; Bogajevskiy, A.; Ponikarovska, S. (EAI Endorsed Transactions on Energy Web, 2020)
Improving the method of regenerative braking of a car with a start-stop system by installing an additional generator is offered. An option of the optimal control of the brake torque of an additional generator is offered. The regenerative braking under consideration required an appropriate method of calculation. This technique makes possible to obtain the dependence of the braking moment on the angular velocity of the generator in various modes, the dependence of the allowable maximum generator power on the speed and load, the dependence of efficiency and the braking moment on the speed. Redistribution of energy generated by an additional generator for charging the battery and heating the engine coolant has been introduced. The brake torque of the electric machine G290 is calculated in the mode of regenerative braking. The obtained results are of practical importance for the transport industry. Calculated N at which the current 150 А is reached. According to factory data the ultimate current is reached at 1450 rpm (discrepancy of less than 3%). So, there is a good coincidence of calculated data. This method does not require a great number of experimental points. The obtained results are of practical importance for the transport industry.
Keywords: start-stop system; mathematical model of synchronous generator; regenerative braking; hybrid car; ecological safety; valve electric drive